Assessment and Management of Cardiorespiratory Deconditioning with Beninese Visually Impaired Subjects - Kora Zaki Yarou, Salifou; Lawani, Mansourou Mohamed; Yessoufou, Lafiou; Kpadonou, Toussaint; Barres, Ismaël (My University, 2019)
This study examined the effects of a short visually impaired subjects. A total of 53 visually impaired pupils and stu-dents in classes B1 = “blind” and B2 “visually impaired” from Benin participated in this study. The submaximal YMCA method was used to obtain accurate and reliable infor-mation about the VO2max of visual impaired subjects. This is a pilot study that surveyed the cardiorespiratory condition of the sraining program on cardiorespiratory condition of Subjects on a cycloergometer before and after 15 workoutsof 30minute each. 68% of visually impaired subjects initially obtained an VO-2max estimate that is very significantly less than 25 mL.kg-1.min-1. All subjects reduced their average exercise heart rate by 13 bpm with average Borg scores of 18.50 (very difficult) for girls and 14.91 (difficult) for boys. The subjects that took part in the study significantly improved their VO2max by 24.31 ± 07 mL.kg-1.min-1for girls and 23.72 ± 10.6 mL.kg-1.min-1forboys (P <0.05). This study showed that total or partial loss of visual function is not a limiting factor in improving the cardiorespiratory capacities of visually impaired people. No correlation was found between the seriousness of the deficiency and the low level of VO2max of the visually impaired.
Keywords: visually impaired subjects; cycloergometer; training program; Benin